Bridge section repair method using high-performance concrete composition for bridge section repair and lightweight formwork
Patent Information
- Application Number
- KR1020250199123
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2045-12-15
Smart Images

Figure 112025141515570-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a high-performance concrete composition for bridge section repair with excellent strength, salt resistance, and workability, and a bridge section repair method using lightweight formwork. Background Technology
[0003] As core structures of transportation infrastructure, bridges undergo various deterioration phenomena, such as cracking, spalling, and rebar corrosion, over time due to continuous exposure to vehicle loads, repetitive fatigue loads, temperature changes, freeze-thaw cycles, salt damage, and atmospheric carbon dioxide. In particular, areas such as bridge substructures, the undersides of upper slabs, piers, and abutments tend to experience accelerated cross-sectional damage due to chloride penetration and the repeated action of moisture.
[0004] Damage to such bridge structures compromises structural safety and shortens their service life; therefore, it is necessary to repair the cross-section and restore durability through periodic repair and reinforcement work. Existing repair materials often require increased water usage to ensure workability, which leads to issues such as reduced strength and decreased durability, including reduced resistance to salt damage caused by increased porosity after hardening.
[0005] Accordingly, there is a growing need for a concrete composition for bridge section repair that offers excellent workability while satisfying physical properties such as strength, salt resistance, and crack resistance.
[0006] Meanwhile, conventional formwork used in cross-section restoration processes is heavy and has a complex installation procedure, making it difficult to apply in high-altitude working environments, and often requires separate support structures for installation.
[0007] This led to problems such as prolonged construction periods and increased traffic control times, resulting in higher social costs. Furthermore, the possibility of safety accidents caused by the detachment or deformation of heavy formwork has been continuously raised. Prior art literature
[0009] Republic of Korea Patent Registration No. 0831087 The problem to be solved
[0010] Therefore, in order to solve the above problems, the present invention provides a concrete composition for bridge section repair that has excellent strength, salt damage resistance, crack resistance, and workability, and furthermore, aims to provide a bridge section repair method using such a composition and a lightweight formwork. means of solving the problem
[0012] To achieve the above objective, the bridge section repair method using the high-performance concrete composition for bridge section repair and lightweight formwork of the present invention (hereinafter referred to as the "method of the present invention") comprises the steps of: removing a deteriorated portion from the repair area of the bridge (S10); installing a formwork made of plastic material on the repair area (S20); and injecting and pouring the high-performance concrete composition for bridge section repair into the repair area of the bridge (S30). The method comprises the step of dismantling the formwork (S40); wherein the high-performance concrete composition for bridge section restoration comprises, for every 100 parts by weight of cement, 300 to 400 parts by weight of mixed silica sand, 20 to 40 parts by weight of latex, 5 to 15 parts by weight of calcium sulfoaluminate-based expansive agent, 3 to 8 parts by weight of silica fume, and 1 to 3 parts by weight of a mixture of montmorillonite and clinoptilolite mixed in a weight ratio of 5:5 to 7:3.
[0013] As an example, in the above step S20, the formwork comprises a plate portion facing the repair area and a grid protruding from the back surface of the plate portion, and is characterized by being fastened to the cross-section of the periphery of the repair area by bolting.
[0014] As one example, the above high-performance concrete composition for bridge section repair is characterized by further including 0.3 to 2 parts by weight of nano alumina per 100 parts by weight of cement.
[0015] delete
[0016] delete
[0017] As one example, the above high-performance concrete composition for bridge section repair is characterized by further including 0.01 to 0.2 parts by weight of tartrate per 100 parts by weight of cement.
[0018] As one example, the above high-performance concrete composition for bridge section repair is characterized by further including 0.5 to 1 weight part of petrolatum per 100 weight parts of cement. Effects of the invention
[0020] As explained above, the method of the present invention utilizes a lightweight formwork that is easy to install and a repair material with excellent physical properties such as compressive strength, workability, salt resistance, and crack resistance, thereby facilitating construction and ensuring structural integrity during repair. Brief explanation of the drawing
[0022] FIG. 1 is a block diagram illustrating the method of the present invention. FIG. 2 is a schematic diagram illustrating the method of the present invention. FIG. 3 is a drawing showing a lightweight formwork applied to the method of the present invention. Figure 4 is a graph showing the particle size of mixed silica sand in the experiment of the present invention. Specific details for implementing the invention
[0023] The present invention will be described in detail below with reference to the attached drawings.
[0024] Since embodiments of the present invention can be modified in various different forms, the scope of the present invention is not limited to the embodiments described below, as it describes general methods that can be utilized through the present invention rather than specifying or implying the limitations of the present invention.
[0026] The method of the present invention is characterized by comprising the steps of: removing a deteriorated portion from a repaired portion of a bridge (S10); installing a lightweight formwork on the repaired portion (S20); injecting and pouring a high-performance concrete composition for bridge section restoration into the repaired portion of the bridge (S30); and dismantling the lightweight formwork (S40).
[0027] First, the method of the present invention includes a step (S10) of removing deteriorated parts from the repair area of the bridge. As shown in FIG. 2, in this step (S10), deteriorated parts can be removed from the rebar cover part as well as the rebar back part in the repair area of the bridge.
[0028] In this step (S10), various known technologies can be applied to remove the deteriorated parts, for example, the guide rail high-pressure spray crushing device presented in Korean Patent Registration No. 2688910 may be applied.
[0029] Next, there is a step (S20) of installing lightweight formwork on the repair area. As shown in FIG. 2, there is a step (S20) of installing lightweight formwork to cover the repair area. As shown in the drawing, after the lightweight formwork is installed to cover the repair area, the lightweight formwork is installed by bolting around the edge of the repair area.
[0030] In this way, lightweight formwork can be attached and detached by bolting in the repair area, making installation and dismantling easy. Also, even in repair areas at high locations such as bridge piers, the formwork is made lightweight, making installation easy and safe.
[0031] Figure 3 shows an example of a lightweight formwork (1). The lightweight formwork (1) of this embodiment is made of plastic material so that the material itself is lightweight.
[0032] The above lightweight formwork (1) includes a plate portion (11) facing the repair area and a grid (12) protruding from the back surface of the plate portion (11), and is fastened to the cross-section of the periphery of the repair area by bolting.
[0033] The above lightweight formwork (1) is composed of a plate (11) and a grid (12) so that it is structurally lightweight and structural reinforcement is achieved through the grid (12).
[0034] The above grid (12) is configured with bolt holes (121), so that adjacent lightweight formwork (1) can be connected by bolting through the bolt holes (121) and used according to the area of the repair area.
[0035] This lightweight formwork (1) is fastened to the cross-section of the area surrounding the repair site by bolting. The structure for bolting the lightweight formwork (1) to the cross-section of the area surrounding the repair site can utilize various known technologies. For example, although not shown in the drawing, bolt holes can be formed in the plate portion (11) to enable bolting to the cross-section of the area surrounding the repair site through the bolt holes.
[0036] Next, there is a step (S30) of injecting and pouring a high-performance concrete composition for bridge section repair into the repair area of the bridge.
[0037] The method involves injecting and pouring a high-performance concrete composition for bridge section restoration between the repair area of the bridge and the lightweight formwork using a known pouring method.
[0038] The above-described high-performance concrete composition for bridge section restoration (hereinafter referred to as the "composition of the present invention") will be explained.
[0039] The composition of the present invention is characterized by comprising 300 to 400 parts by weight of mixed silica sand, 20 to 40 parts by weight of latex, 5 to 15 parts by weight of calcium sulfoaluminate-based expansive agent, and 3 to 8 parts by weight of silica fume, based on 100 parts by weight of cement.
[0040] The above cement functions as a binder and forms an alkaline protective film of passivation on the surface of the reinforcing bar. It is appropriate to use Portland cement as specified in KS L 5201.
[0041] The above mixed silica sand is intended to form an aggregate skeleton for the cement paste to ensure the density and shape stability of the cross-section restoration layer, and when mixed in the range of 300 to 400 parts by weight, sufficient filling ability and age strength can be secured without reducing workability.
[0042] The above latex is a powder or liquid polymer binder that functions to improve interfacial adhesion between the cross-section repair layer and the base concrete and to increase initial crack resistance. In particular, when formulated in the range of 20 to 40 parts by weight, durability is improved by the film-forming effect without excessive viscosity increase, and resistance to repeated impact and load is increased.
[0043] In addition, the calcium sulfoaluminate-based expansive agent (CSA-based expansive agent) plays a role in compensating for microcracks caused by autogenous shrinkage and drying shrinkage by inducing the formation of ettringite upon early hydration, and it is preferable to incorporate it in an amount of 5 to 15 parts by weight. Within this range, the expansion compensation effect is stably exhibited, and it is possible to suppress long-term expansion or strength impairment phenomena that may occur when added excessively.
[0044] The above silica fume is an ultrafine pozzolanic material that reacts with Ca(OH)₂, a byproduct of cement hydration, to form a dense CSH gel and reduce capillary pores, thereby improving chloride ion penetration resistance and overall durability performance. In the present invention, silica fume is incorporated in an amount of 3 to 8 parts by weight to improve the long-term strength and watertightness of the cross-section repair material, while preventing problems such as reduced dispersibility and increased viscosity that may occur due to excessive addition.
[0045] Therefore, the basic composition of the present invention can secure a balanced combination of strength, adhesion, workability, and salt resistance required for a cement-based cross-section repair material, and provides performance suitable for cross-section repair of structures subject to repeated loading and significant environmental deterioration factors, such as bridges.
[0046] Meanwhile, the present invention provides an example in which montmorillonite is further added in addition to the above compositions to control the whitening phenomenon.
[0047] Efflorescence is caused by salts (Na₂S) generated during the cement hydration process. + , K + , Ca 2 + This phenomenon occurs when calcium carbonate dissolves in pore water, travels to the surface via capillary pores, and reacts with carbon dioxide in the air to form white crystals on the surface. This whitening phenomenon affects not only the appearance but also physical properties, such as reduced salt resistance, by causing micropores to form on the surface.
[0048] Accordingly, in the present invention, montmorillonite is added, and the montmorillonite has a layered structure and carries a negative charge structurally, so salts (Na₂S) + , K + , Ca 2 + It is to control the whitening phenomenon by adsorbing (etc.).
[0049] However, when only montmorillonite is added, there may be a problem with reduced workability due to the high specific surface area and moisture adsorption capacity, and there may be a problem with cracking caused by the swelling of the interlayers due to moisture absorption.
[0050] Accordingly, the present invention provides an example in which clinoptilolite is further added to montmorillonite.
[0051] In the case of clinoptilolite, cation adsorption capacity is also exhibited, but it is lower than that of montmorillonite, whereas it lacks swelling ability, so the decrease in workability can be compensated for and cracking can be compensated for.
[0052] That is, it is reasonable to add a mixture of montmorillonite and clinoptilolite so that efflorescence control ability is expressed through alkali inhibition, while workability and crack resistance are compensated for, and the mixing ratio is 1 to 3 parts by weight per 100 parts by weight of cement, and it is preferable to limit the mixing ratio to (5:5) to (7:3).
[0053] In addition, the present invention provides an example in which 0.3 to 2 parts by weight of nanoalumina are further included to further increase salt resistance. The addition of nanoalumina promotes the nucleation of CSH and CASH generation, thereby further lowering the chloride ion diffusion coefficient and improving compressive strength.
[0054] Preferably, it is appropriate to mix 0.3 to 2 parts by weight of nano alumina per 100 parts by weight of cement, and the particle size is limited to 10 to 50 nm.
[0055] However, when only nanoalumina is added, insoluble precipitates such as nanoalumina aggregation and Al(OH)3-like precipitates are formed, and these insoluble precipitates may cause a decrease in interfacial (ITZ) adhesion and strength.
[0056] Accordingly, the present invention presents an example in which strength is further enhanced by controlling the formation of precipitates through the additional inclusion of 0.01 to 0.2 parts by weight of tartrate. By the addition of tartrate, Ca 2 + , Al 3 + By forming a complex (chelate) with it, the change in free ion concentration is moderated, thereby suppressing rapid precipitation / aggregation of hydration products.
[0057] Meanwhile, when only nanoalumina is added, there may be a problem in that resistance to long-term cracking is reduced due to self-shrinkage / drying shrinkage caused by the densification of the paste. To compensate for this, the present invention provides an example in which 0.5 to 1 weight part of petrolatum is additionally included.
[0058] Petrolatum is a semi-solid hydrophobic hydrocarbon material that exists as a fine dispersed phase within the concrete matrix and functions to improve long-term crack resistance.
[0059] In other words, petrolatum acts as a ductile inclusion within the concrete matrix, suppressing the initiation and propagation of cracks caused by long-term deterioration factors such as drying shrinkage, autogenous shrinkage, and cyclic loading, thereby providing results that effectively improve the long-term crack resistance of concrete.
[0061] An embodiment of the present invention is described below through experimental examples.
[0062] As shown below, each sample was prepared, and in each example, the mixed silica sand had the particle size distribution shown in Table 1 and Figure 4 below, and each example was prepared by mixing the W / C ratio to 35%.
[0064] division No. 2 No. 3 No. 4 No. 5 No. 6 No. 7 Synthetic particle size distribution (%) 30 10 20 15 15 10
[0066] <Example 1>
[0067] A sample was prepared by mixing 350 parts by weight of mixed silica sand, 30 parts by weight of latex, 10 parts by weight of CSA-based expansive agent, and 5 parts by weight of silica fume for every 100 parts by weight of cement.
[0069] <Example 2>
[0070] A sample was prepared by mixing in the same way as in Example 1, but including an additional 2 parts by weight of montmorillonite.
[0072] <Example 3>
[0073] A sample was prepared by mixing in the same way as in Example 1, but including an additional 2 parts by weight of clinoptilolite.
[0075] <Example 4>
[0076] A sample was prepared in the same manner as in Example 1, but with an additional 2 parts by weight of montmorillonite and clinoptilolite, mixed in a weight ratio of 6:4.
[0078] <Example 5>
[0079] A sample was prepared in the same manner as in Example 1, except that 1.0 weight part of nanoalumina was additionally incorporated.
[0081] <Example 6>
[0082] A sample was prepared in the same manner as in Example 5, except that 0.05 parts by weight of tartrate were additionally incorporated.
[0084] <Example 7>
[0085] A sample was prepared in the same manner as in Example 6, but with an additional 0.7 parts by weight of petrolatum added.
[0087] In the following, tests were performed on the above examples for compressive strength (KS F 2405), chloride ion penetration resistance (KS F 2608), change in length (KS F 2424, measured from 1 to 28 years of age), slump (KS F 2402), plastic viscosity (ASTM C1749), and whitening, and the results are presented in Table 2 below.
[0088] The experiment on whitening was conducted by visually testing the samples 60 days after preparation, and scores were assigned to each sample in a total of 6 sections: no whitening (0 points), slight whitening (formation of a very thin film, 1 point), weak whitening (formation of a thin powder film, 2 points), moderate whitening (crystalline lattice / flow marks visible, 3 points), severe whitening (large crystal thickness, obscuring surface texture, 4 points), and severe whitening (thick crystal layer / red appearance, 5 points).
[0090] division Compressive strength (MPa, 28 days) Chloride ion penetration resistance (coulomb, 28 days) Rate of change in length (%) Slump Flow (mm) Plastic viscosity (Pa.s) White flower (60 days) Example 1 43 408 0.033 400 67.5 3 Example 2 44 375 0.038 385 72.0 0 Example 3 45 390 0.034 395 68.5 2 Example 4 46 380 0.034 390 68.0 1 Example 5 49 285 0.041 390 70.5 3 Example 6 53 280 0.036 400 68.1 3 Example 7 52 275 0.031 395 68.3 3
[0092] First, Example 1 showed that silica fume, latex, and CSA expansion agents worked in harmony to achieve a 28-day compressive strength of 43 MPa, a chloride ion penetration of 408 C, and a length change rate of 0.033%, thereby securing sufficient strength and salt resistance for bridge section repair. In addition, the slump flow of 400 mm and plastic viscosity of 67.5 Pa·s are at a level that maintains good workability.
[0093] Comparing Examples 2 and 3, it can be seen that when only montmorillonite is added to control whitening, the whitening control ability is excellent, but there are issues with reduced workability and cracking due to swelling, whereas when only clinoptilolite is added, the whitening control ability is lower than that of montmorillonite, but there are no issues with reduced workability and crack resistance. Accordingly, it can be seen that by adding a mixture of these as in Example 4, the whitening control ability is exhibited while the reduced workability and crack resistance can be compensated for.
[0094] When comparing Examples 1 and 5, it can be seen that in the case of Example 5, the addition of nanoalumina increases salt resistance compared to Example 1, while there is a problem with reduced long-term crack resistance.
[0095] Meanwhile, in the case of Example 6, it can be seen that the strength is improved while maintaining salt resistance as more tartrate is added in addition to nanoalumina, which is attributed to controlling the formation of precipitates due to the addition of nanoalumina.
[0096] In addition, it can be seen that in the case of Example 7, petrolatum is further included to supplement long-term crack resistance. Explanation of the symbols
[0098] 1 : Lightweight formwork 11 : Panel 12 : Grid
Claims
Claim 1 A method for repairing a bridge section using a high-performance concrete composition and a lightweight formwork, comprising: a step of removing a deteriorated portion from a repaired portion of a bridge (S10); a step of installing a formwork made of plastic material on the repaired portion (S20); a step of injecting and pouring a high-performance concrete composition for bridge section repair into the repaired portion of the bridge (S30); and a step of dismantling the formwork (S40); wherein the high-performance concrete composition for bridge section repair comprises, for every 100 parts by weight of cement, 300 to 400 parts by weight of mixed silica sand, 20 to 40 parts by weight of latex, 5 to 15 parts by weight of a calcium sulfoaluminate-based expansive agent, 3 to 8 parts by weight of silica fume, and 1 to 3 parts by weight of a mixture of montmorillonite and clinoptilolite mixed in a weight ratio of 5:5 to 7:
3. Claim 2 A concrete composition for high-performance bridge section repair and a bridge section repair method using a lightweight formwork, characterized in that, in step S20, the formwork comprises a plate portion facing the repair area and a grid protruding from the back surface of the plate portion, and is fastened to the cross-section of the peripheral portion of the repair area by bolting. Claim 3 delete Claim 4 delete Claim 5 In claim 1, the high-performance concrete composition for bridge section repair is characterized by further including 0.3 to 2 parts by weight of nano alumina per 100 parts by weight of cement, and a bridge section repair method using lightweight formwork. Claim 6 In claim 5, the high-performance concrete composition for bridge section repair is characterized by further including 0.01 to 0.2 parts by weight of tartrate per 100 parts by weight of cement, and a bridge section repair method using a lightweight formwork. Claim 7 In claim 6, the high-performance concrete composition for bridge section repair is characterized by further including 0.5 to 1 weight part of petrolatum per 100 weight parts of cement, and a bridge section repair method using lightweight formwork.
Citation Information
Patent Citations
Manufacturing method of water proofing agent
KR100276795B1
Renewal and reform method for detrioration area atexposured reinforced steel concrete
KR100335826B1
Composite for concrete pavement and reparing method of concrete pavement using the composite
KR101090243B1
Plant-mix type drainage additive for modified asphalt, and the manufacturing method thereof
KR101183909B1
Concrete repair material and cross sectional concrete surface repair and recovery method using the same
KR101675325B1
